2018
DOI: 10.1101/375337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LDpred-funct: incorporating functional priors improves polygenic prediction accuracy in UK Biobank and 23andMe data sets

Abstract: 15Genetic variants in functional regions of the genome are enriched for complex trait heritabil-16 ity. Here, we introduce a new method for polygenic prediction, LDpred-funct, that leverages 17 trait-specific functional enrichments to increase prediction accuracy. We fit priors using the 18 recently developed baseline-LD model, which includes coding, conserved, regulatory and LD-19 related annotations. We analytically estimate posterior mean causal e↵ect sizes and then use 20 cross-validation to regularize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 63 publications
1
84
2
Order By: Relevance
“…Despite these limitations, our study highlights the impact of negative selection on the genetic architecture across complex traits and in different functional genomic regions. In addition to better understanding of the genetic architecture, our methods can also be applied to genetic mapping and polygenic risk prediction through the use of the joint SNP effect estimates or the characterised underlying distributions of effect sizes as prior knowledge for other methods 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, our study highlights the impact of negative selection on the genetic architecture across complex traits and in different functional genomic regions. In addition to better understanding of the genetic architecture, our methods can also be applied to genetic mapping and polygenic risk prediction through the use of the joint SNP effect estimates or the characterised underlying distributions of effect sizes as prior knowledge for other methods 45 .…”
Section: Discussionmentioning
confidence: 99%
“…We applied SuSiE and PolyFun + SuSiE to fine-map 47 traits in the UK Biobank, including 31 traits analyzed in refs. 34,35 , 9 blood cell traits analyzed in ref. 12 , and 7 recently released metabolic traits (average N=317K; Supplementary Table 5), using the same data and the same parameter settings described in the Finemapping simulations section.…”
Section: Functionally Informed Fine-mapping Of 47 Complex Traits In Tmentioning
confidence: 99%
“…12 , and 7 recently released metabolic traits (average N=317K; Supplementary Table 5), using the same data and the same parameter settings described in the Finemapping simulations section. We performed basic QC on each trait as described in our previous publications 34,35 . Specifically, we removed outliers outside the reasonable range for each quantitative trait, and quantile normalizing within sex strata after correcting for covariates for non-binary traits with non-normal distributions.…”
Section: Functionally Informed Fine-mapping Of 47 Complex Traits In Tmentioning
confidence: 99%
“…Additionally, the use of multiple related phenotypes has been demonstrated to enhance the predictive power of PS [47]; for example, the combination of educational attainment and intelligence GWAS may permit a doubling of cognitive ps 2 [48]. Finally, it has recently been suggested that enrichment of certain subcategories of functional variation (e.g., coding, conserved, regulatory, and LD-related genomic annotations) in GWAS results can be leveraged to further enhance prediction accuracy [49,50].…”
Section: Discussionmentioning
confidence: 99%